Hierarchically structured Co@Fe(SA)-MoO/MoP electrocatalyst with tuned electronic states for thermodynamically optimized hydrogen adsorption in chloride-rich media - Islam, Muhaiminul; Hong, Jongwoo; Park, Kanguk; Patil, Amar M.; Kim, Taehyeon; Das, Sushanta K.; Yu, Seungho; Jun, Seong Chan (Royal Society of Chemistry, 2025)
To address the challenges of sustainable hydrogen production, we present a hierarchically structured electrocatalyst comprising an Fe single-atom (SA)-doped MoO/MoP heterojunction anchored on porous Co nanorods (Co@Fe(SA)-MoO/MoP). Systematic optimization of the d-band center enables precise tuning of hydrogen adsorption energetics, leading to exceptional bifunctional activity for both the HER and OER. In chloride-rich media, the catalyst achieves ultralow overpotentials of 169 mV (HER) and 260 mV (OER) at 200 mA cm−2, while demonstrating outstanding durability with ∼93% and ∼88% retention after 40 h of operation at 100 mA cm−2. When deployed in an anion-exchange membrane water electrolyzer (AEMWE), the heterostructure requires only 2.11 V at 0.5 A cm−2, surpassing commercial Pt/C‖RuO2 benchmarks. Furthermore, the integrated electrolyzer exhibits a low cell voltage of 1.62 V at 100 mA cm−2 in 1.0 M KOH, highlighting its potential for scalable green hydrogen production.